Serum interleukin-40 increases in anti-AchR antibody-positive myasthenia gravis and correlates with disease activity - Jia, Kun; Shao, Yingzhe; Tan, Taofeng; Liu, Xuan; Zhang, Qiuxia; Zhao, Ning; Yang, Li (Frontiers in Neurology, 2025)
BackgroundInterleukin-40 (IL-40), as an immune regulatory factor discovered in recent years, mainly plays a role in B-cell-related immune responses and is involved in the pathological processes of various inflammatory diseases, autoimmune disorders, and infectious diseases. However, its role in myasthenia gravis (MG) has rarely been reported.MethodsWe used enzyme-linked immunosorbent assay (ELISA) to measure the serum IL-40 levels in 58 MG patients and 55 healthy controls, and conducted a detailed analysis of the clinical data.ResultsThe serum IL-40 level in MG patients was significantly higher than that in healthy controls (p < 0.0001). After immunotherapy, the serum IL-40 level in MG patients significantly decreased (p < 0.0001). In MG, the IL-40 level of severe patients was significantly higher than that of mild patients (p < 0.0001). The ROC curve determined that the cut-off value for distinguishing IL-40 in MG from healthy controls was 15.63 pg/mL, with an AUC of 0.846 (95% CI: 0.773–0.919), 74.1% specificity, and 85.5% sensitivity.ConclusionThe serum IL-40 level in MG patients is elevated and is correlated with the severity of the disease. High levels of IL-40 may serve as a specific indicator for monitoring disease activity, which supports its potential as a non-invasive biomarker for disease monitoring.